Pabrik Bulu Mata Palsu dan Ruang Kuasa Perempuan Buruh (Kajian Etnografis di Desa Pasunggingan, Kecamatan Pengadegan, Kabupaten Purbalingga, Jawa Tengah) - Nurlaili Khikmawati (Empower : Jurnal Pengembangan Masyarakat Islam, 2020)
The study regarding women labor is always interesting to done. This is due to the domestic roles of women that women labor has a double burden for work in the factory and work in the household/domestic area. In addition, the placement of women in the domestic area makes "labor" is not always statistically calculated as a job and the work status of women remains as a housewife. Another challenge faced by women when working as labor is the emergence of public assumptions about the existence of women's power in the household, including their power to sue for divorce. These assumptions about the domestic life of women labor encourage researcher to conduct a study of the power of women (labor) in the household as an effect of industrialization, in terms of access and control over resources and decision making in the household. This research was conducted using ethnographic methods in Pasunggingan Village, Pengadegan Subdistrict, Purbaingga Regency, Central Java as one of the villages that has a high number of women labors. The results of this study revealed that the establishment of a false eyelash industry in the village area had attracted women in Pasunggingan Village to conduct economic migration. This migration is carried out for a variety of reasons both economic and non-economic which impact on the income of women (and households) and changes in the lifestyle of women and society. The entry of women into the industrial sector has made women has a higher bargaining value in the household and can open a household into a wider area.